Difference between revisions of "Nesbitt's Inequality"

m
(categories)
Line 1: Line 1:
'''Nesbitt's [[Inequality]]''' is a theorem which, although rarely cited, has many instructive proofs.  It states that for positive <math> \displaystyle a, b, c </math>,
+
'''Nesbitt's [[Inequality]]''' is a theorem which, although rarely cited, has many instructive proofs.  It states that for positive <math>a, b, c </math>,
 
<center>
 
<center>
 
<math>
 
<math>
Line 21: Line 21:
 
</math>,
 
</math>,
 
</center>
 
</center>
with equality when all the <math> \displaystyle a_i </math> are equal.
+
with equality when all the <math>a_i </math> are equal.
  
 
== Proofs ==
 
== Proofs ==
Line 27: Line 27:
 
=== By Rearrangement ===
 
=== By Rearrangement ===
  
Note that <math> \displaystyle a,b,c </math> and <math> \frac{1}{b+c} = \frac{1}{a+b+c -a}</math>,  <math> \frac{1}{c+a} = \frac{1}{a+b+c -b} </math>, <math> \frac{1}{a+b} = \frac{1}{a+b+c -c} </math> are sorted in the same order.  Then by the [[rearrangement inequality]],
+
Note that <math>a,b,c </math> and <math> \frac{1}{b+c} = \frac{1}{a+b+c -a}</math>,  <math> \frac{1}{c+a} = \frac{1}{a+b+c -b} </math>, <math> \frac{1}{a+b} = \frac{1}{a+b+c -c} </math> are sorted in the same order.  Then by the [[rearrangement inequality]],
 
<center>
 
<center>
 
<math>
 
<math>
Line 33: Line 33:
 
</math>.
 
</math>.
 
</center>
 
</center>
For equality to occur, since we changed <math>{} a \cdot \frac{1}{b+c} + b \cdot \frac{1}{c+a} </math> to <math> b \cdot \frac{1}{b+c} + a \cdot \frac{1}{c+a} </math>, we must have <math> \displaystyle a=b </math>, so by symmetry, all the variables must be equal.
+
For equality to occur, since we changed <math>{} a \cdot \frac{1}{b+c} + b \cdot \frac{1}{c+a} </math> to <math> b \cdot \frac{1}{b+c} + a \cdot \frac{1}{c+a} </math>, we must have <math>a=b </math>, so by symmetry, all the variables must be equal.
  
 
=== By Cauchy ===
 
=== By Cauchy ===
Line 49: Line 49:
 
</math>,
 
</math>,
 
</center>
 
</center>
as desired.  Equality occurs when <math> \displaystyle (b+c)^2 = (c+a)^2 = (a+b)^2 </math>, i.e., when <math> \displaystyle a=b=c </math>.
+
as desired.  Equality occurs when <math>(b+c)^2 = (c+a)^2 = (a+b)^2 </math>, i.e., when <math>a=b=c </math>.
  
 
We also present three closely related variations of this proof, which illustrate how [[AM-HM]] is related to [[AM-GM]] and Cauchy.
 
We also present three closely related variations of this proof, which illustrate how [[AM-HM]] is related to [[AM-GM]] and Cauchy.
Line 71: Line 71:
 
</math>.
 
</math>.
 
</center>
 
</center>
Setting <math> \displaystyle x = b+c, y= c+a, z= a+b </math>, we expand the left side to obtain
+
Setting <math>x = b+c, y= c+a, z= a+b </math>, we expand the left side to obtain
 
<center>
 
<center>
 
<math>
 
<math>
Line 77: Line 77:
 
</math>,
 
</math>,
 
</center>
 
</center>
which follows from <math> \frac{x}{y} + \frac{y}{x} \ge 2 </math>, etc., by [[AM-GM]], with equality when <math> \displaystyle x=y=z </math>.
+
which follows from <math> \frac{x}{y} + \frac{y}{x} \ge 2 </math>, etc., by [[AM-GM]], with equality when <math>x=y=z </math>.
  
 
==== By AM-HM ====
 
==== By AM-HM ====
Line 93: Line 93:
 
</math>.
 
</math>.
 
</center>
 
</center>
Setting <math> \displaystyle x=b+c, y=c+a, z=a+b </math> yields the desired inequality.
+
Setting <math>x=b+c, y=c+a, z=a+b </math> yields the desired inequality.
  
 
=== By Substitution ===
 
=== By Substitution ===
  
The numbers <math> \displaystyle x = \frac{a}{b+c}, y = \frac{b}{c+a}, z = \frac{c}{a+b} </math> satisfy the condition <math> \displaystyle xy + yz + zx + 2xyz = 1 </math>.  Thus it is sufficient to prove that if any numbers <math> \displaystyle x,y,z </math> satisfy <math> \displaystyle xy + yz + zx + 2xyz = 1 </math>, then <math> x+y+z \ge \frac{3}{2} </math>.
+
The numbers <math>x = \frac{a}{b+c}, y = \frac{b}{c+a}, z = \frac{c}{a+b} </math> satisfy the condition <math>xy + yz + zx + 2xyz = 1 </math>.  Thus it is sufficient to prove that if any numbers <math>x,y,z </math> satisfy <math>xy + yz + zx + 2xyz = 1 </math>, then <math> x+y+z \ge \frac{3}{2} </math>.
  
Suppose, on the contrary, that <math> x+y+z < \frac{3}{2} </math>.  We then have <math> \displaystyle xy + yz + zx \le \left( \frac{x+y+z}{3} \right)^2 < \frac{3}{4} </math>, and <math> 2xyz \le 2 \left( \frac{x+y+z}{3} \right)^3 < \frac{1}{4} </math>.  Adding these inequalities yields <math> \displaystyle xy + yz + zx + 2xyz < 1 </math>, a contradiction.
+
Suppose, on the contrary, that <math> x+y+z < \frac{3}{2} </math>.  We then have <math>xy + yz + zx \le \left( \frac{x+y+z}{3} \right)^2 < \frac{3}{4} </math>, and <math> 2xyz \le 2 \left( \frac{x+y+z}{3} \right)^3 < \frac{1}{4} </math>.  Adding these inequalities yields <math>xy + yz + zx + 2xyz < 1 </math>, a contradiction.
  
 
=== By Normalization and AM-HM ===
 
=== By Normalization and AM-HM ===
  
We may normalize so that <math> \displaystyle a+b+c = 1 </math>.  It is then sufficient to prove
+
We may normalize so that <math>a+b+c = 1 </math>.  It is then sufficient to prove
 
<center>
 
<center>
 
<math>
 
<math>
Line 113: Line 113:
 
=== By Weighted AM-HM ===
 
=== By Weighted AM-HM ===
  
We may normalize so that <math> \displaystyle a+b+c =1 </math>.
+
We may normalize so that <math>a+b+c =1 </math>.
  
 
We first note that by the [[rearrangement inequality]],
 
We first note that by the [[rearrangement inequality]],
Line 128: Line 128:
 
</center>
 
</center>
  
Since <math> \displaystyle a+b+c = 1 </math>, weighted AM-HM gives us
+
Since <math>a+b+c = 1 </math>, weighted AM-HM gives us
 
<center>
 
<center>
 
<math>
 
<math>
Line 134: Line 134:
 
</math>.
 
</math>.
 
</center>
 
</center>
 +
 +
[[Category:Inequality]]
 +
[[Category:Theorem]]

Revision as of 14:14, 26 October 2007

Nesbitt's Inequality is a theorem which, although rarely cited, has many instructive proofs. It states that for positive $a, b, c$,

$\frac{a}{b+c} + \frac{b}{c+a} + \frac{c}{a+b} \ge \frac{3}{2}$,

with equality when all the variables are equal.

All of the proofs below generalize to proof the following more general inequality.

If $a_1, \ldots a_n$ are positive and $\sum_{i=1}^{n}a_i = s$, then

$\sum_{i=1}^{n}\frac{a_i}{s-a_i} \ge \frac{n}{n-1}$,

or equivalently

$\sum_{i=1}^{n}\frac{s}{s-a_i} \ge \frac{n^2}{n-1}$,

with equality when all the $a_i$ are equal.

Proofs

By Rearrangement

Note that $a,b,c$ and $\frac{1}{b+c} = \frac{1}{a+b+c -a}$, $\frac{1}{c+a} = \frac{1}{a+b+c -b}$, $\frac{1}{a+b} = \frac{1}{a+b+c -c}$ are sorted in the same order. Then by the rearrangement inequality,

$2 \left( \frac{a}{b+c} + \frac{b}{c+a} + \frac{c}{a+b} \right) \ge \frac{b}{b+c} + \frac{c}{b+c} + \frac{c}{c+a} + \frac{a}{c+a} + \frac{a}{a+b} + \frac{b}{a+b} = 3$.

For equality to occur, since we changed ${} a \cdot \frac{1}{b+c} + b \cdot \frac{1}{c+a}$ to $b \cdot \frac{1}{b+c} + a \cdot \frac{1}{c+a}$, we must have $a=b$, so by symmetry, all the variables must be equal.

By Cauchy

By the Cauchy-Schwarz Inequality, we have

$[(b+c) + (c+a) + (a+b)]\left( \frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b} \right) \ge 9$,

or

$2\left( \frac{a+b+c}{b+c} + \frac{a+b+c}{c+a} + \frac{a+b+c}{a+b} \right) \ge 9$,

as desired. Equality occurs when $(b+c)^2 = (c+a)^2 = (a+b)^2$, i.e., when $a=b=c$.

We also present three closely related variations of this proof, which illustrate how AM-HM is related to AM-GM and Cauchy.

By AM-GM

By applying AM-GM twice, we have

$[(b+c) + (c+a) + (a+b)] \left( \frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b} \right) \ge 3 [(b+c)(c+a)(a+b)]^{\frac{1}{3}} \cdot \left(\frac{1}{(b+c)(c+a)(a+b)}\right)^{\frac{1}{3}} = 9$,

which yields the desired inequality.

By Expansion and AM-GM

We consider the equivalent inequality

$[(b+c) + (c+a) + (a+c)]\left( \frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b} \right) \ge 9$.

Setting $x = b+c, y= c+a, z= a+b$, we expand the left side to obtain

$3 + \frac{x}{y} + \frac{y}{x} + \frac{y}{z} + \frac{z}{y} + \frac{z}{x} + \frac{x}{z} \ge 9$,

which follows from $\frac{x}{y} + \frac{y}{x} \ge 2$, etc., by AM-GM, with equality when $x=y=z$.

By AM-HM

The AM-HM inequality for three variables,

$\frac{x+y+z}{3} \ge \frac{3}{\frac{1}{x} + \frac{1}{y} + \frac{1}{z}}$,

is equivalent to

$(x+y+z) \left(\frac{1}{x} + \frac{1}{y} + \frac{1}{z}\right) \ge 9$.

Setting $x=b+c, y=c+a, z=a+b$ yields the desired inequality.

By Substitution

The numbers $x = \frac{a}{b+c}, y = \frac{b}{c+a}, z = \frac{c}{a+b}$ satisfy the condition $xy + yz + zx + 2xyz = 1$. Thus it is sufficient to prove that if any numbers $x,y,z$ satisfy $xy + yz + zx + 2xyz = 1$, then $x+y+z \ge \frac{3}{2}$.

Suppose, on the contrary, that $x+y+z < \frac{3}{2}$. We then have $xy + yz + zx \le \left( \frac{x+y+z}{3} \right)^2 < \frac{3}{4}$, and $2xyz \le 2 \left( \frac{x+y+z}{3} \right)^3 < \frac{1}{4}$. Adding these inequalities yields $xy + yz + zx + 2xyz < 1$, a contradiction.

By Normalization and AM-HM

We may normalize so that $a+b+c = 1$. It is then sufficient to prove

$\frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b} \ge \frac{9}{2}$,

which follows from AM-HM.

By Weighted AM-HM

We may normalize so that $a+b+c =1$.

We first note that by the rearrangement inequality,

$3 (ab + bc + ca) \le a^2 + b^2 + c^2 + 2(ab + bc + ca)$,

so

$\frac{1}{a(b+c) + b(c+a) + c(a+b)} \ge \frac{1}{\frac{2}{3}(a+b+c)^2} = \frac{3}{2}$.

Since $a+b+c = 1$, weighted AM-HM gives us

$a\cdot \frac{1}{b+c} + b \cdot \frac{1}{c+a} + c \cdot \frac{1}{a+b} \ge \frac{1}{a(b+c) + b(c+a) + c(a+b)} \ge \frac{3}{2}$.

Invalid username
Login to AoPS